Cover Image, Volume 139, Issue 20. Issue 20 (15th March 2022) - Nagayama, Kei; Morris, Barry A.; Matsuba, Go; Nakata, Kazuyuki
Abstract : This image by Kei Nagayama, BarryMorris, GoMatsuba, and Kazuyuki Nakata shows the possible ionomeric structure of poly(ethylene‐ co ‐methacrylic acid) ionomers neutralized by zinc (left), zinc and sodium (center) and sodium (right), where double circles and red dots represent ionic multiplets and cation‐acid lone pair, respectively. X‐ray scattering indicated that the sodium cations appear to promote zinc cations to be incorporated into ionic multiplets and form a new ionic multiplet where both cations are included. Thus, the enhanced properties of the co‐neutralized ionomer are ascribed to the change in the distribution of cationacid. DOI: 10.1002/app.52126